2022
DOI: 10.1186/s12936-022-04067-z
|View full text |Cite
|
Sign up to set email alerts
|

Malaria prevalence and performance of diagnostic tests among patients hospitalized with acute undifferentiated fever in Zanzibar

Abstract: Background Control efforts in Zanzibar reduced the burden of malaria substantially from 2000 to 2015, but re-emergence of falciparum malaria has been observed lately. This study evaluated the prevalence of malaria and performance of routine diagnostic tests among hospitalized fever patients in a 1.5 years period in 2015 and 2016. Methods From March 2015 to October 2016, paediatric and adult patients hospitalized with acute undifferentiated fever at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…RDT reported in this study is similar to that reported for the CareStar Malaria p.f/p.v (Pf-HRP2/Pv-pLDH) combo test in low-transmission areas in Ethiopia [ 17 ]. However, previous studies in declining malaria transmission or pre-elimination settings demonstrated reduced performance of light microscopy and different Pf-HRP2-based or Pf-HRP2/pLDH combo RDTs [ 33 , 40 , 41 , 42 , 43 ]. On the other hand, a study in a low-transmission region of Senegal reported high sensitivity and specificity for the CareStar Malaria Pf-HRP2/Pv-pLDH combo RDT (97.3% and 94.1%, respectively) and microscopy (93.2% and 100%, respectively) compared with PCR [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…RDT reported in this study is similar to that reported for the CareStar Malaria p.f/p.v (Pf-HRP2/Pv-pLDH) combo test in low-transmission areas in Ethiopia [ 17 ]. However, previous studies in declining malaria transmission or pre-elimination settings demonstrated reduced performance of light microscopy and different Pf-HRP2-based or Pf-HRP2/pLDH combo RDTs [ 33 , 40 , 41 , 42 , 43 ]. On the other hand, a study in a low-transmission region of Senegal reported high sensitivity and specificity for the CareStar Malaria Pf-HRP2/Pv-pLDH combo RDT (97.3% and 94.1%, respectively) and microscopy (93.2% and 100%, respectively) compared with PCR [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The implications of missed infections are signi cant, as prompt and accurate diagnosis is crucial for timely treatment and preventing disease progression. Low parasitemia has been identi ed in other studies as a limitation when considering RDTs for malaria diagnosis [29]- [32]. False negatives detected by RDTs could potentially be attributed to pfhrp-2 gene deletions, mutations, or the prozone effect, as reported by other studies.…”
Section: Discussionmentioning
confidence: 72%
“…Considering the challenges of microscopy as a diagnostic tool for malaria in rural Tanzania, the substantial number of patients that tested positive with BFM would have exacerbated the number of incorrect malaria diagnoses and treatments prescribed together with the potentially false positive clinical diagnoses [17,18]. On the other hand, the relatively low proportion of malaria positive rates among the RDT tested individuals may contribute in fuelling concerns over the extent of false negatives that are still being observed on Mainland Tanzania and Zanzibar [50,51]. While not perceived a major immediate concern, it was stressed that clinicians should be aware of the risk.…”
Section: Discussionmentioning
confidence: 99%